Pertumbuhan dan Hasil Tanaman Kedelai Pada Pemberian Pupuk Fosfor dan Bakteri Pelarut Fosfat - Sagala, Danner; Handayani, Witri; Nurseha, Nurseha (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
Soil fertility on marginal land is a significant challenge in increasing soybean productivity. This study aimed to determine the response of soybean growth and production to providing phosphate solubilizing bacteria and phosphorus fertilizers. The experiment with two factors was arranged with a randomized block design. Phosphorus fertilizers were evaluated in four dose levels, namely 0, 100, 200, and 300 kg ha-1. Each phosphorus fertilizer dose treatment was combined with two phosphate solubilizing bacteria levels, 0 and 150 kg ha-1. The results showed that the best phosphorus fertilizer treatment was at a dose of 200 kg ha-1, producing the best results on the observation variable of seed production results per plot. The best phosphate solvent treatment was a dose of 150 kg ha-1, which gave the best seed production results on the observation variable per plot. There was no interaction between phosphorus fertilizer and phosphate solubilizing bacteria on the growth and yield of soybean plants.